2009
DOI: 10.1080/00498250902769967
|View full text |Cite
|
Sign up to set email alerts
|

In vitrostability and metabolism of salvinorin A in rat plasma

Abstract: Salvinorin A is the main active psychoactive ingredient in Salvia divinorum, a Mexican plant that has been widely available as a hallucinogen in recent years. The aims of this study were to investigate the stability of salvinorin A in rat plasma, esterases responsible for its degradation, and estimation of the degradation products. The apparent first-order rate constants of salvinorin A at 37 degrees C, 25 degrees C, and 4 degrees C were 3.8 x 10(-1), 1.1 x 10(-1), and < 6.0 x 10(-3) h(-1), respectively. Salvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 18 publications
1
53
0
1
Order By: Relevance
“…The first investigation dedicated to tracking the metabolism of salvinorin A in vitro was conducted by Tsujikawa et al (2009). By monitoring rat plasma samples, the contribution of several esterases relevant to human subjects could be monitored, including acetylcholinesterase, butyrylcholinesterase, arylesterase, and carboxylesterase.…”
Section: A Metabolism Of Salvinorin Amentioning
confidence: 99%
“…The first investigation dedicated to tracking the metabolism of salvinorin A in vitro was conducted by Tsujikawa et al (2009). By monitoring rat plasma samples, the contribution of several esterases relevant to human subjects could be monitored, including acetylcholinesterase, butyrylcholinesterase, arylesterase, and carboxylesterase.…”
Section: A Metabolism Of Salvinorin Amentioning
confidence: 99%
“…Salvinorin A is degraded by several cytochrome oxidase isoenzymes, including CYP 2D6, CYP1A1, CYP2C18, and CYP2E1 [170]. One ex vivo study demonstrated that salvinorin A is hydrolyzed to an inactive metabolite, salvinorin B by blood esterases [171].…”
Section: Pharmacology/pharmacokineticsmentioning
confidence: 98%
“…4A), which implied that the plasma esterase was the main factor leading to the instability of OB. KF was suggested to be an effective plasma esterase inhibitor [12,13], which had been successfully used to solve the problem of instability of drugs in plasma [14][15][16]. Also, the method of immediately adding acetonitrile to freshly collected plasma could prevent the hydrolysis of drugs by esterase [17].…”
Section: Stability and Sample Preparationmentioning
confidence: 99%